The Types of Communication Strategies Used by The English Teacher of SLB Negeri 1 Gianyar in Teaching Deaf or Hard of Hearing Students - N.K.M Dewi (Journal of Psychology and Instruction, 2018)
This present study aimed at finding out the types of communication strategies used by the English teacher to communicate with D/HH students during teaching and learning process in the classroom, the teacher’s reason used those communication strategies and whether the teacher communicate with each student the same ways or not. This present study was a case study with qualitative approach. The subject of this study was an English teacher of Senior High School who teach D/HH students in SLB Negeri 1 Gianyar. The data was collected by using observation sheet, interview guide, and audio-video recorded. Then, the data was analyzed descriptively by using three steps, namely data reduction, data display, and conclusion drawing or verification. The results of the study show that there are 7 types of communication strategies used by the English teacher to communicate with D/HH students, namely: lips or speech reading, sign language, cued speech, total communication, conceptual language, visual media, and literal translation. The main reason why the English teacher used those communication strategies was in order to ease him to communicate with D/HH students and help him in explaining the material toward D/HH students. Then, it was found that the English teacher used different communication strategies to communicate with each student. Based on the finding above, the teacher used all types of communication strategies in every class and supported by logical reasons.